Avaliação do co-cultivo de bactérias e microalga Chlorella sorokiniana no tratamento de efluentes - Dutra, Júlia Fonseca (Universidade Federal de São Carlos, 2021)
Pollution is a social and health problem, the lack of sewer treatment together with its incorrect disposal are one of the leading sources of aquatic pollution. Microalgae are microorganisms which have the potential for tertiary sewer treatment since they are resistant to temperature and luminosity variations, are able to synthesize organic compounds from carbon dioxide, providing sustenance for heterotrophic organisms, such as bacterias, who will decompose it and recycle it. On the other hand, some bacteria use the produced oxygen by the microalgae and produce compounds that increase vegetal growth. The objective of this study was to verify bacteria and microalgae C. sorokiniana capacity to promote microalgal growth and remove nutrients from the system. With that considered, four batches were analyzed, comparing microorganisms’ performance in piggery effluent and in the UASB reactor effluent from Monjolinho’s Sewage Treatment Station, evaluating the co-culture and aeration influence in microalgal growth, as well as the dissolved phosphorus and nitrogen removal. Four different samples were evaluated: microalgae alone, with biofilm bacteria consortia, with phosphorus solubilizing bacteria and with IAA (indole acetic acid) producer bacteria. All four batches were carried in 2-liter flasks with 1 liter of effluent volume, at 27ºC (±4ºC) with 12/12 hours photoperiod and inoculated with 105 and 104 cell/ml microalgae and bacteria, respectively. The results obtained with the UASB reactor effluent were superior to those with piggery effluent, achieving 107 cell/ml. Analyzing cellular growth, none of the consortia reached superior results when compared to microalgae alone. However, when analyzing phosphorus and nitrogen removal, the consortia with the phosphorus solubilizing bacteria stood out, achieving phosphorus removal of 84% from the initial concentration. Therefore, aiming for the effluent treatment and nutrient removal, the C. sorokiniana and phosphorus solubilizing bacteria consortia have showed itself promising.
Evaluation of bacteria and microalgae Chlorella sorokiniana co-culture in the wastewater treatment
Keywords: Consórcio de microalgas e bactérias; Nitrogênio total dissolvido; Fósforo total dissolvido; Ácido indol acético (AIA); Chlorella sorokiniana; Microalgae and bacteria consortia; Dissolved nitrogen; Dissolved phosphorus; Indole acetic acid (IAA).; CIENCIAS BIOLOGICAS::MICROBIOLOGIA::MICROBIOLOGIA APLICADA